Potential Use of GLP-1 and GIP/GLP-1 Receptor Agonists for Respiratory Disorders: Where Are We at? - Miodrag Janić; Sabina Škrgat; Matevž Harlander; Mojca Lunder; Andrej Janež; Anca Pantea Stoian; Mohamed El-Tanani; Viviana Maggio; Manfredi Rizzo (Medicina)
Chronic respiratory disorders are the third leading cause of mortality globally. Consequently, there is a continuous pursuit of effective therapies beyond those currently available. The therapeutic potential of the glucagon-like peptide-1 (GLP-1) and the glucose-dependent insulinotropic polypeptide/GLP-1 (GIP/GLP-1) receptor agonists extends beyond the regulation of glycemia, including glucometabolic, cardiovascular, and renal effects, rendering them viable candidates, due to their mechanisms of action, for the possible treatment of respiratory disorders. This manuscript aims to provide a comprehensive evaluation of the evidence on potential direct (cellular) and indirect (metabolic) actions of GLP-1 and GIP/GLP-1 receptor agonists within the pulmonary systems. In addition, it examines their efficacy in addressing prevalent respiratory disorders, specifically chronic obstructive pulmonary disease (COPD), asthma, pneumonia, obstructive sleep apnea, pulmonary hypertension, lung cancer, and lung transplantation. Finally, the manuscript seeks to identify potential avenues for further focused research in this field.